HUBUNGAN MALOKLUSI GIGI TERHADAP STATUS PSIKOSOSIAL REMAJA (LITERATURE REVIEW) - Muhiddin Muhiddin; Diana Wibowo; Galuh Dwinta Sari (Dentin, 2022)
ABSTRACTBackground: Malocclusion is a condition in which the occlusion deviates from the normal form. Malocclusion can be measured using the IOTN and DAI indices. Research has shown that adolescents who experience problems with anterior dental malocclusion can negatively affect their psychosocial status. Measurement of the effect of malocclusion on psychosocial status can be determined using a questionnaire method, namely the Psychosocial Impact of Dental Aesthetic Questionnaire (PIDAQ). Objective: To analyze the relationship between dental malocclusion and the psychosocial status of adolescents aged 12-18 years. Methods: This study uses a literature review method with a narrative review model. The literature search was carried out using sources from Google Scholar and PubMed. The literature that has been obtained is then selected according to the inclusion criteria, collected, analyzed, and interpreted. Results: The relationship between dental malocclusion on the psychosocial status of adolescents aged 12-18 years as measured using the IOTN and DAI indexes stated that there was a significant effect. Conclusion: Dental malocclusion has an impact on the psychosocial status of adolescents. Keywords: Adolescent psychosocial, Dental malocclusion, Malocclusion, Psychosocial. ABSTRAKLatar Belakang: Maloklusi merupakan kondisi dimana oklusi yang menyimpang dari bentuk normal. Maloklusi dapat diukur dengan menggunakan indeks IOTN dan DAI. Penelitian telah menunjukkan bahwa remaja yang mengalami masalah maloklusi gigi dapat berpengaruh negatif terhadap status psikososialnya. Pengukuran pengaruh maloklusi terhadap status psikososial dapat diketahui menggunakan metode kuesioner yaitu Psychosocial Impact of Dental Aesthetic Questionnaire (PIDAQ). Tujuan: Menganalisis hubungan maloklusi gigi terhadap status psikososial remaja usia 12-18 tahun. Metode: Penelitian ini menggunakan metode literature review dengan model narrative review. Penelusuran literatur dilakukan menggunakan sumber dari Google Scholar dan PubMed. Literatur yang telah didapatkan kemudian diseleksi sesuai kriteria inklusi dikumpulkan, dianalisis, dan dilakukan interpretasi. Hasil: Hubungan antara maloklusi gigi terhadap status psikososial remaja usia 12-18 tahun yang diukur menggunakan indeks IOTN dan DAI menyatakan terdapat pengaruh signifikan. Kesimpulan: Maloklusi gigi berdampak pada kondisi status psikososial remaja.  Kata Kunci: Maloklusi, Maloklusi gigi anterior, Psikososial, Psikososial remaja